IDENTIFIKASI PERJANJIAN KERJA KARYAWAN KONTRAK MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI PT. BIMA BUDIDAYA MUTIARA (BBM) DESA PIONG KECAMATAN SANGGAR KABUPATEN BIMA - Saddam, Saddam (IJTIMAIYA: Journal of Social Science and Teaching, 2019)
Lately, the arising problems in an internal company, from pattern making to culminate in unrest will contract employees in the company's status as a reasonably long time. Empowerment of employees contract in effect executed in full, but the employees who belong to particular time work agreements are not fully hired thoroughly. Up to now, there are indications the granting of jobs generally passes regardless of the official rules of the applicable employment contract agreement. The method used was qualitative. Data collection method using observation, documentation, interviews, and triangulation. Data analysis was conducted in three stages namely data reduction, the presentation of the data, and draw conclusions. The results showed that certain time work agreements first and further led to the emergence of the rights and obligations of the parties. There are a number of principles in the implementation of the employment contract agreement is not yet based on the procedure of employment rules. The incidence of unrest because of a few things: a surfeit of employees will be a contract worker status for too long, the company less heed to the things that can be counted as wages, and the pattern of the Division of work within the time period for contract employees in the realm of shifts. The company's efforts in coping with disquiet the contract employee will do some of the following, namely; the efforts of some employees into contract adoption workers, pay attention to things that can be counted as wages, and equitable patterns of Division of the period of time in work for the employee's contract in the realm of shifts.